(untitled) (GEOMATE Journal, 2024)
The ultimate load is known as the ultimate strength of a structure. It is the maximum load a structure can withstand before collapsing. Structural reinforcement is needed for structures experiencing low strength due to dead load, live load, fatigue load, and earthquakes. In this research, Glass Fiber Reinforced Polymer (GFRP) shows a highly viable solution because of its benefits, encompassing exceptional corrosion resistance, lightweight properties, high strength, ease of installation, and commendable durability. This research aimed to compare the three sample groups to evaluate the effect of GFRP on reinforced concrete beams. The collected data included assessments of maximum load and deflection. Test specimens were constructed in three sets of distinct variations. The first set comprised concrete beams reinforced without GFRP, designated as control beams (BN), totaling three pieces. The second set entailed concrete beams reinforced with GFRP, labeled as BG. The third variation consisted of reinforced concrete beams subjected to collapse or post-ultimate load conditions and subsequently strengthened with GFRP, labeled as BGPU. The purpose is to observe the influence of GFRP-S reinforcement on reinforcing three beams. The analysis showed that direct GFRP-reinforced beams exhibited load increases ranging from 13.59% to 29.76% compared to control beams. In the case of post-ultimate load GFRP reinforcement, load enhancements of 6.80% to 16.78% were observed. These results showed the potential of GFRP reinforcement in repairing damaged beams, providing a viable solution for structural enhancement.